Comparison of the efficacy and safety between different oral P2Y12 receptor inhibitors in patients with acute coronary syndrome: a systematic review and meta-analysis. (3rd October 2022) - Lepone, A; Castiglione, V; Gentile, F; Scalera, S; Negro, F; Ridolfi, L; Favilli, M; Italiano, A; Mazzola, M; Masaracchia, G; Mancini, S; Guarini, G; et al.
Abstract: Introduction: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor inhibitor for at least 1 month is the mainstay of therapy after an acute coronary syndrome (ACS). Despite several randomized controlled trials (RCTs) having compared different DAPT regimens after an ACS, the choice of the optimal P2Y12 receptor inhibitor is still debated. Purpose: We aimed to compare the efficacy and safety profiles of the new P2Y12 receptor inhibitors (prasugrel and ticagrelor) versus clopidogrel in patients with ACS through a meta-analysis of RCTs. Methods: We performed an extensive literature search, from January 1970 to December 2021 using PubMed database. Studies were eligible if they were RCTs directly comparing different oral P2Y12 receptor inhibitors in patients with ACS. Data on study methods, patient characteristics, and outcomes of interest (all-cause and cardiovascular death, recurrent myocardial infarction, stroke, major and non-major bleeding) were extracted from the original publications. We performed a meta-analysis using a random-effects model with the Mantel–Haenszel method. The effect measures of each study included were calculated and reported as odds ratio (OR) with 95% confidence interval (CI), visually presented in forest plots. A two-sided p-value <0.05 was considered statistically significant. Heterogeneity was tested using the I 2 -statistic. Results: A total of 117 studies were available for the analysis; after full reading 11 studies were eligible to be analyzed. The 11 studies reported data on 50, 722 patients: 25, 424 [50.1%] taking a new oral P2Y12 receptor inhibitor and 25, 298 [49.9%] taking clopidogrel. Patients receiving ticagrelor or prasugrel showed a lower risk of all-cause mortality (OR 0.88, 95% confidence interval [CI] 0.80–0.97, I 2 =8%), cardiovascular mortality (OR 0.88, 95% CI 0.81–0.95, I 2 =0%), and recurrent myocardial infarction (OR 0.86, 95% CI 0.76–0.97, I 2 =43%) compared to those receiving clopidogrel. The two groups did not differ significantly concerning the risk of stroke (OR 0.98, 95% CI 0.82–1.17, I 2 =0%), major bleeding (OR 1.05, 95% CI 0.97–1.15, I 2 =0%), or non-major bleeding (OR 1.36, 95% CI 0.85–2.20, I 2 =67%). By restricting the analysis to the studies comparing ticagrelor versus clopidogrel, the ticagrelor group showed a lower risk of all-cause mortality (OR 0.79, 95% CI 0.70–0.90, I 2 =0%), but a higher risk of non-major bleeding (OR 1.67, 95% CI 1.05–2.66, I 2 =30%). There was no significant difference between ticagrelor and clopidogrel in terms of cardiovascular death (OR 0.87, 95% CI 0.73–1.05, I 2 =0%), stroke (OR 1.06, 95% CI 0.85–1.13, I 2 =0%), or major bleeding (OR 1.02, 95% CI 0.93–1.12, I 2 =0%). Conclusions: In patients with an ACS, a DAPT strategy with aspirin plus either prasugrel or ticagrelor is associated with a reduced risk of all-cause and cardiovascular mortality as well as of recurrent myocardial infarction compared to aspirin plus clopidogrel, without an increased risk of bleeding. Funding Acknowledgement: Type of funding sources: None.